Extraction of FM components from speech signals using all-pole model - Thiruvaran, T.; Ambikairajah, E.; Epps, J. (My University, 2008)
Frequency modulation has recently emerged as a promising model for characterising the phase of a speech signal. Proposed is a novel technique for extracting the frequency modulation (FM) components from the subband speech signal, using a second-order all-pole model. Evaluation of a speaker recognition system employing FM features, extracted using the proposed technique, on the NIST 2001 database reveals improvement over MFCC baseline and significant improvements over the discrete energy separation algorithm and a Hilbert transform based approach in terms of equal error rate.